Establishment of the first international standard for PEGylated granulocyte colony stimulating factor (PEG-G-CSF): Report of an international collaborative study - Wadhwa, Meenu (J Immunol Methods, 2015)
We assessed the feasibility of developing a suitable international reference standard for determination of in vitro biological activity of human sequence recombinant PEG-G-CSF products with a 20 kD linear PEG linked to the N-terminal methionyl residue of G-CSF (INN Filgrastim), produced using a conjugation process and coupling chemistry similar to that employed for the lead PEGfilgrastim product. Based on initial data which showed that the current WHO 2nd international standard, IS for G-CSF (09/136) or alternatively, a PEG-G-CSF standard with a unitage traceable to the G-CSF IS may potentially serve as the IS for PEG-G-CSF products, two candidate preparations of PEG-G-CSF were formulated and lyophilized at NIBSC. These preparations were tested by 23 laboratories using in vitro bioassays in a multi-centre collaborative study. Results indicated that on the basis of parallelism, the current WHO 2nd IS for G-CSF or any of the PEG-G-CSF samples could be used as the international standard for PEG-G-CSF preparations. However, because of the variability in potency estimates seen when PEG-G-CSF preparations were compared with the current WHO 2nd IS for G-CSF, a candidate PEG-G-CSF was suitable as the WHO IS. The preparation 12/188 was judged suitable to serve as the WHO IS based on in vitro biological activity data. Therefore, the preparation coded 12/188 was established by the WHO Expert Committee on Biological Standardization (ECBS) in 2013 as the WHO 1st IS for human PEGylated G-CSF with an assigned in vitro bioactivity of 10,000 IU per ampoule.